IS THERE A STRUCTURAL IMPROVEMENT IN THE MERCHANDISE EXPORTS OF THE BALKAN COUNTRIES IN THE PERIOD 2000-2012? - Nikolić, Goran (Economic Annals, 2013)
The value of indicators of the similarity of Balkan countries’ exportand import structuresto those of developed countries grew only mildly, which indicates that the unfavourable structure of exports has been retained. While similarity coefficients increased in the period until and including 2012, they failed to reach a critical turning point as in advanced European countries in transition. In practically all Balkan economies, since 2000 the technological intensity and the factor intensity of foreign trade have changed toward an increased share of highly-processed products, but the share of skill-intensive manufactures remained almost two times smaller than in developed economies. An aggravating factor was the continual strong double-digit growth of exports in most Balkan countries, which ‘forced’ exports based on the existing inappropriate structure and prevented a change in export structure. Balkan countries would have to attract FDI in export sectors that are capital- or skilled-labour-intensive. A targeted industrial policy and sector- and firm-level strategies are necessary to give momentum to a shift towards technology-intensive activities, associated with higher spillover effects. It is realistic to expect that the evolution of the economic system through restructuring would additionally improve the still unfavourable structural characteristics of Balkan countries’ exports.